The Sustainable Development Goals Report 2020 - United Nations Department of Economic; Social Affairs (United Nations, 2020)
This year marks the start of the Decade of Action to deliver the Sustainable Development Goals by 2030. It is a critical period to advance a shared vision and accelerate responses to the world’s gravest challenges – from eliminating poverty and hunger to reversing climate change. Yet, in only a brief period of time, the precipitous spread of the novel coronavirus turned a public health emergency into one of the worst international crises of our lifetimes, changing the world as we know it. Now, due to COVID-19, an unprecedented health, economic and social crisis is threatening lives and livelihoods, making the achievement of Goals even more challenging. The Sustainable Development Goals Report 2020 presents an overview of progress towards the SDGs before the pandemic started, but it also looks at some of the devastating initial impacts of COVID-19 on specific Goals and targets. The report was prepared by the United Nations Department of Economic and Social Affairs in collaboration with over 200 experts from more than 40 international agencies using the latest available data and estimates.